Assessment of oxidative stress in dairy cows supplemented prepartum with vitamin E and selenium with reference to retention of fetal membranes - GUPTA, SANDEEP KUMAR; KUMAR, HARENDRA; MORE, T (The Indian Journal of Animal Reproduction, 2023)
The occurrence of retention of fetal membranes (RFM), the levels of lipid peroxide {LPO, indices of oxidative stress) andplasma cortisol were studied in cows following prepartum supplementation of 1100 JU Vit. E and 30 mg selenium. The prepartumsupplementation of vit. E and selenium alleviated the incidence of RFM from 12 to 0%. The injection of vit. E and seleniumsignificantly (P < 0.01) reduced the LPO levels at 0 wk prepartum. A significant (P < 0.01) increase in LPO levels (3.67±0.16 Vs2.46±0.07 nanomoles MDNmg of Hb) was noticed from 3 to 0 wk inthose cows which experienced RFM. Furthermore, a significant(P < 0.05) increase was observed in plasma cortisol level (60.50±4.33 Vs 25.64±6.26 ng/ml) at prepartum period in RFM cows ascompared to non-RFM. It can be concluded that the prepartum supplementation of Vit. E and Se reduced the levels of LPO andthereby the incidence of RFM.
Keywords: Cows; retention of fetal membranes; vit. E; selenium; oxidative stress; lipid peroxide and cortisol